2011
DOI: 10.3109/10408444.2011.554794
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive toxicants have a threshold of adversity

Abstract: This paper surveys the scientific basis for the current threshold approach for reproductive hazard and risk assessment. In some regulatory areas it was recently suggested to consider reproductive toxicants under the stringent linear extrapolation risk assessment paradigm that was developed for genotoxic carcinogens. First, the current risk assessment paradigm for genotoxic carcinogens is addressed, followed by an overview of reproductive toxicology and its threshold dose approach for hazard and risk assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 83 publications
0
28
0
Order By: Relevance
“…Processes believed to be driven by the interaction of toxicants with non-DNA cellular constituents are often evaluated by assuming a threshold dose below which no effect is expected. Toxicologists generally acknowledge and support the existence of homeostatic mechanisms and employ the supposition that adverse effects occur only when these mechanisms are saturated or overloaded [Piersma et al, 2011]. As a result, a NOEL can be derived from the dose-response information generated for safety assessment studies.…”
Section: Discussionmentioning
confidence: 99%
“…Processes believed to be driven by the interaction of toxicants with non-DNA cellular constituents are often evaluated by assuming a threshold dose below which no effect is expected. Toxicologists generally acknowledge and support the existence of homeostatic mechanisms and employ the supposition that adverse effects occur only when these mechanisms are saturated or overloaded [Piersma et al, 2011]. As a result, a NOEL can be derived from the dose-response information generated for safety assessment studies.…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with the basic principles of toxicology, a recent evaluation of data on reproductive toxicants indicated that both the dose and the window of exposure determine the outcome (Piersma et al, 2011). Accordingly, if a substance causes critical adverse effects within a window of susceptibility, this still requires a dose above a certain level (Piersma et al, 2011).…”
Section: Windows Of Susceptibility and Data Requirementsmentioning
confidence: 97%
“…It has been reported that the TTC for general toxicity can also be applied to both the developmental and reproductive toxicity endpoints (Laufersweiler et al, 2012). Piersma et al concluded that all endpoints in reproductive toxicology have shown thresholds of adversity, thus there is evidence for the presence of dose levels with no appreciable increase in risk (Piersma et al, 2011). For reproductive toxicity, the same TTC values have been suggested as for general toxicity, given that NOAELs of reproductive toxicity studies tend to be similar or higher than those observed in general toxicity studies (Kroes et al, 2007).…”
Section: Inmentioning
confidence: 98%